Report on industrial attachment in PowerSeraya Ltd - Tan, Yanxin. (2010)
This report describes the knowledge and experience gained during the Industrial Attachment (IA) programme. In this program, I was attached to Pulau Seraya Power Station for 22 weeks. Throughout this period, I went to different departments to learn about the different power generating plants and auxiliary systems and took on projects in the respective departments. An example of the project done was pump overhaul. To ensure that the plant is able to run continuously and reliably, regular maintenance has to be done on the equipments. Other than overhauls, I was also given a chance to research on the occurrence of flow assisted corrosion (FAC) on the HRSG LP drum cyclone separator walls. In conclusion, the IA program had provided me with basic technical skills as well as other essential working skills such as communication, researching and presenting skills to prepare me for the workforce in future.